ANALYSIS OF COST AND TIME PERFORMANCE ON THE EAST SURABAYA HOSPITAL CONSTRUCTION PROJECT USING THE EARNED VALUE METHOD - Almi, Harfandi; Hanie Teki Tjendani; Budi Witjaksana (International Journal Science and Technology, 2024)
The construction of the East Surabaya Hospital is a multiyear project, starting from 2023 to 2024. The project has a contract value of Rp. This 494,603,098,000 is funded by the Regional Revenue and Expenditure Budget (APBD) of the Surabaya City Government. This research aims to analyze the cost and time performance of the project. The method used is the earned value method. The results of the cost and time performance analysis using the Earning Value method show that the cost performance and time performance of the East Surabaya Hospital Construction in the 22nd (twenty-second) week is considered not good. This result is shown by the Cost Variance value of Rp. - 608,118,565 and Schedule Variance value Rp. - 44,410,784,255. The Cost Performance Index value of 0.996 and the Schedule Performance Index value of 0.76 also shows that the cost and time performance of this project in the 22nd (twenty-second) week is not in good condition.